Systematic review of carbon-neutral building technologies (CNBTs) by climate groups and building types - Lee, Gyueun; Avelina, Nadia; Rim, Donghyun; Chi, Seokho; Ahn, Hyeunguk (Journal of Building Engineering, 2023)
As buildings are responsible for approximately 40% of global greenhouse gas emissions, existing literature provides information about the impacts of carbon-neutral building technologies (CNBTs). However, these impacts can vary across different climate groups and building types. To address this research gap, we conducted a comprehensive review of 65 peer-reviewed papers that focused on state-of-the-art CNBTs. To quantitatively compare the impacts of CNBTs, pre- and post-energy use intensities as well as payback periods were investigated. The results show notable differences in energy saving potentials depending on the climate group. However, regardless of local climate, carbon reduction potential is greater for non-residential than residential buildings. The building type also influences the optimal payback periods for CNBTs. Overall, the review results suggest that for countries with limited time and resources, CNBTs could be firstly implemented to non-residential buildings and gradually extended to residential buildings. Furthermore, the study findings reveal that rather than relying upon a single technology alone, integrating other building design features with CNBTs, such as renewable energy sources or system improvements, can effectively reduce the undesirably long payback periods, thereby ultimately achieving carbon neutrality with econmic feasibility.
Keywords: Building technologies; Building types; Carbon neutralities; Carbon neutrals; Energy-use intensities; Greenhouse gas emissions; Net-zero building; Payback periods; Residential building; Systematic Review; Carbon neutrality; Energy use intensity; Net-zero buildings; Payback periods; Systematic review